Combined Metabolic Activators Accelerates Recovery in Mild‐to‐Moderate COVID‐19. Issue 17 (28th June 2021) - Altay, Ozlem; Arif, Muhammad; Li, Xiangyu; Yang, Hong; Aydın, Mehtap; Alkurt, Gizem; Kim, Woonghee; Akyol, Dogukan; Zhang, Cheng; Dinler‐Doganay, Gizem; Turkez, Hasan; Shoaie, Saeed; et al.
Abstract: COVID‐19 is associated with mitochondrial dysfunction and metabolic abnormalities, including the deficiencies in nicotinamide adenine dinucleotide (NAD + ) and glutathione metabolism. Here it is investigated if administration of a mixture of combined metabolic activators (CMAs) consisting of glutathione and NAD+ precursors can restore metabolic function and thus aid the recovery of COVID‐19 patients. CMAs include l ‐serine, N ‐acetyl‐l ‐cysteine, nicotinamide riboside, and l ‐carnitine tartrate, salt form of l ‐carnitine. Placebo‐controlled, open‐label phase 2 study and double‐blinded phase 3 clinical trials are conducted to investigate the time of symptom‐free recovery on ambulatory patients using CMAs. The results of both studies show that the time to complete recovery is significantly shorter in the CMA group (6.6 vs 9.3 d) in phase 2 and (5.7 vs 9.2 d) in phase 3 trials compared to placebo group. A comprehensive analysis of the plasma metabolome and proteome reveals major metabolic changes. Plasma levels of proteins and metabolites associated with inflammation and antioxidant metabolism are significantly improved in patients treated with CMAs as compared to placebo. The results show that treating patients infected with COVID‐19 with CMAs lead to a more rapid symptom‐free recovery, suggesting a role for such a therapeutic regime in the treatment of infections leading to respiratory problems. Abstract : Open‐label phase‐2 and double‐blinded phase‐3 clinical trials show that administration of CMA accelerates the recovery of ambulatory COVID‐19 patients. By integrating clinical data with plasma metabolomics and inflammatory proteomics, it is shown that CMA improves immune response and regulates antioxidant, amino acid, and lipid metabolism. It is observed that administration of CMA is an effective and safe therapeutic strategy for COVID‐19 patients.